The rebellion of the bases against the standardization of pedagogical work: The case of the mobilization against the Teaching Career Law in Chile - Sisto, Vicente; Núñez Parra, Lorena.; López Barraza, Andrea.; Ramírez Casas Del Valle, Lorena Pía. (Arizona State University, 2022)
There has been a great insistence that the installation of teacher performance standards would be one of the main means to improve educational quality. In 2015, the Chilean government presented a bill that establishes a professional development system based on performance standards set at the central level. These regulate pedagogical training and the evaluation of the performance that classifies teachers, establishing salaries, professional development and sanctions, including expulsion from the system. During the processing of the bill, one of the most important teacher mobilizations in recent years took place. This article analyzes (a) how defenders of the project built the mobilization in opinion columns and editorials; (b) how it was described and justified in documents of the movement itself; and (c) how it is narrated by a sample of leaders who participated in it. Although the promoters of the policy constructed the mobilization as a mere corporatist expression of interest groups, the documents of the movement and interviews reveal the emergence of a voice that reveals concrete, joint pedagogical practice, situated in the school, as the main reference of teaching work and of what should be relevant evaluation and career development policies
A rebelião das bases contra a estandardização do trabalho pedagógico: O caso da mobilização contra a Lei da Carreira Docente no Chile.
La Rebelión de las bases frente a la estandarización del Trabajo Pedagógico: El caso de la movilización contra la ley de carrera docente en Chile
Keywords: Política educativa; Evaluación de profesores; Profesores; Calidad de la educación